2020
DOI: 10.1007/s00167-020-06258-0
|View full text |Cite
|
Sign up to set email alerts
|

A web-based machine-learning algorithm predicting postoperative acute kidney injury after total knee arthroplasty

Abstract: PurposeAcute kidney injury (AKI) is a deleterious complication after total knee arthroplasty (TKA). The purposes of this study were to identify preoperative risk factors and develop a web‐based prediction model for postoperative AKI, and assess how AKI affected the progression to ESRD. MethodThe study included 5757 patients treated in three tertiary teaching hospitals. The model was developed using data on 5302 patients from two hospitals and externally validated in 455 patients from the third hospital. Eighte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 29 publications
(38 reference statements)
0
53
0
Order By: Relevance
“…In clinical situations in which several variables need to be comprehensively assessed, as in the diagnosis of septic arthritis of the knee, machine-learning algorithms have promise as a new approach. Several studies have revealed machine-learning algorithms to be superior to logistic regression at predicting perioperative risks of arthroplasty or patient-reported outcome measures after arthroscopy [ 10 , 13 , 17 ]. The authors of the present study obtained higher prediction accuracy using the XGBoost algorithm than synovial WBC count.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In clinical situations in which several variables need to be comprehensively assessed, as in the diagnosis of septic arthritis of the knee, machine-learning algorithms have promise as a new approach. Several studies have revealed machine-learning algorithms to be superior to logistic regression at predicting perioperative risks of arthroplasty or patient-reported outcome measures after arthroscopy [ 10 , 13 , 17 ]. The authors of the present study obtained higher prediction accuracy using the XGBoost algorithm than synovial WBC count.…”
Section: Discussionmentioning
confidence: 99%
“…Importance scores indicate how valuable a feature is in the construction of boosted trees within the model. In recent studies applying the gradient boost algorithm, the authors tried to infer the decision-making process by referring to the feature importance applied to the tree decision [ 9 , 10 ]. Synovial WBC count and serum uric acid level, which were significant in the multivariate analysis (Table 1 ), also showed high importance in the XGBoost algorithm (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The total number of subjects tested in the included studies was 304,076, with the sample size ranged from 109 to 96,653 [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] .…”
Section: Characteristics Of Eligible Studiesmentioning
confidence: 99%
“…Classification models predicting high-risk groups and survival regression models such as random survival forest was mainly used in prognostic models using supervised machine-learning algorithm. [11][12][13] The classification model facilitates the interpretation of the result clearly. Risk status, sensitivity, and specificity data provide clear insight .249 0 (0) Age at onset of pain, y 28.9 ± 9.4 20.9 ± 9.6 22.9 ± 6.…”
Section: Modeling Strengthsmentioning
confidence: 99%